2010
DOI: 10.2106/jbjs.j.00277
|View full text |Cite
|
Sign up to set email alerts
|

Review of Successful Litigation Against English Health Trusts in the Treatment of Adults with Orthopaedic Pathology

Abstract: These findings highlight the fact that education and vigilance remain important components of orthopaedic training as many of the cases of successful litigation had a preventable cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 7 publications
(5 reference statements)
3
50
0
1
Order By: Relevance
“…Costs were calculated from Clegg et al 12 and Atrey et al 9 for screening, treatment and potential litigation. This framework was then applied to the results of the treatment protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs were calculated from Clegg et al 12 and Atrey et al 9 for screening, treatment and potential litigation. This framework was then applied to the results of the treatment protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Litigation concerning missed diagnosis of DDH is increasing 8. Atrey et al 9 examined the National Health Service Litigation Authority over a 10-year period and found that DDH was the third most common cause in paediatric orthopaedics with an average cost of £48 534.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2000 and 2006, there were 73 successful cases of litigation, related to trauma of the foot and ankle, in the UK 73. Each received an average payment equivalent to $125,773 73…”
Section: Methodsmentioning
confidence: 99%
“…This specialty was chosen because it is associated with a relatively high level of harm 12. For example, from 2000 to 2006, an equivalent of US$321 million was paid in adult orthopaedic surgery-related negligence settlements in the UK 13. Similar figures were reported the Physician Insurers Association of America 14…”
Section: Introductionmentioning
confidence: 97%